Analysis of the Digital Marketing Mix on the Mikhayla_Shop Account Reviewed from the Perspective of Islamic Business Ethics: Analisis Digital Marketing Mix pada akun Mikhayla_Shop ditinjau dari perspektif Etika Bisnis Islam - Saqofa Nabilah Aini; Luqita Romaisyah; Riska Agustin (El-Qist: Journal of Islamic Economics and Business (JIEB), 2023)
This study aims to analyze the form of the digital marketing mix through social media on the Instagram account mikhayla_shop in terms of Islamic Business Ethics. The formulation of the problem in the study is how the digital marketing mix through social media studies on the Instagram account mikhayla_shop is viewed from an Islamic perspective?;. This study uses qualitative research methods with a descriptive approach. Primary data sources come from interviews, observations, and document studies with owners and employees of the Mikhayla shop. At the same time, the secondary data sources come from books, information sources, archives, and official personal documents. Structured interviews and indirect observation are the techniques of data collection. The results showed that Mikayla shop's digital marketing mix through social media is based on Islamic Business Ethics.